The Influence of Product Innovation And Market Orientation On The Competitive Advantages of Fried Red Onion SMEs In Sumenep District - Fatmawati Fatmawati; Dina Kurniawati; Moh. Kurdi (Agricultural Science, 2022)
SMEs have advantages compared to large businesses, among others: flexibility and quickly adapt to market changes, able to absorb relatively large unskilled labor, the majority of SMEs produce consumer goods and services with low elasticity of demand for income. With the majority of Indonesia's population having relatively low education, the ability of SMEs to absorb unskilled labor is very helpful in creating a workforce. The population in this study is the Small and Medium Enterprises (UKM) of Red Fried Onion in Basoka Village, Rubaru District, Sumenep Regency with a total of 20 SMEs. From the existing population, the sample in this study used the entire population, namely the perpetrators of the Red Fried Onion SMEs in Basoka, Rubaru District. The purpose of the study was to determine the effect of product innovation on the market orientation of Fried Onion SMEs in Sumenep Regency, to determine the effect of product innovation on the competitive advantage of Fried Red Onion SMEs in Sumenep Regency and to determine market orientation to the competitive advantages of Fried Red Onion SMEs in Sumenep Regency. The research method used in this study is to use data analysis techniques in this study using Partial Least Square (PLS). From the results of the study it can be concluded that market innovation has a significant positive effect on market orientation, product innovation has a significant positive effect on competitive advantage and market orientation has a significant positive effect on competitive advantage.